Two consecutive successful live birth in woman with 17α hydroxylase deficiency by frozen–thaw embryo transfer under hormone replacement endometrium preparation. (4th May 2018) - Kitajima, Michio; Miura, Kiyonori; Inoue, Tsuneo; Murakami, Yuko; Kitajima, Yuriko; Murakami, Naoko; Taniguchi, Ken; Yoshiura, Ko-Ichiro; Masuzaki, Hideaki
Abstract: 17α-Hydroxylase deficiency is rare autosomal recessive disorder that manifested by hypertension, hypokalemia, delayed sexual development, primary amenorrhea and infertility. The information regarding infertility care and conception in women with this disorder are extremely limited. We report a 24-year-old Japanese woman with primary amenorrhea who was diagnosed as partial 17α-hydroxylase deficiency caused by homozygous 3 bp deletion in exon 1 of 17α-hydroxylase gene. In vitro fertilization with controlled ovarian stimulation was carried out and all viable embryo were frozen. During ovarian stimulation, serum progesterone levels were markedly elevated, and endometrial growth was impaired. Utilizing frozen-thaw embryo transfer under hormonal replacement (glucocorticoid, estradiol and progesterone), she had successfully given two consecutive live birth. Women with 17α-hydroxylase deficiency with residual ovarian reserve can afford reproductive success by appropriate diagnosis and treatment by assisted reproductive technology.